Inflammation and Oxidative Stress via Persistent Hyperglycemia in Progression of Diabetic Nephropathy in Type 2 Diabetes Mellitus - Kafle, D; Islam, N; Aryal, B; Adhikary, P; Singh, Neelina (Journal of Chitwan Medical College, 2013)
Diabetic nephropathy is a major microvascular complication of diabetes, representing the leading cause of end stage renal disease in the world, and a major cause of morbidity and mortality in type 2 diabetic subjects. In the kidney, a number of pathways that generate reactive oxygen species (ROS) such as glycolysis, specific defects in the polyol pathway, uncoupling of nitric oxide synthase, xanthine oxidase, NAD (P) H oxidase, and advanced glycation have been identified as potentially major contributors to the pathogenesis of diabetic kidney disease. Changes in oxidative stress biomarkers, including superoxide dismutase, catalase, glutathione reductase, glutathione peroxidase, glutathione levels, vitamins, lipid peroxidation, nitrite concentration, nonenzymatic glycosylated proteins have been associated with diabetic nephropathy due to oxidative stress induced hyperglycemia. Oxidative stress in diabetes is responsible for endothelial dysfunction releasing inflammatory markers cytokines from the damaged renal tissue. Hyperglycemia induces intracellular reactive oxygen species in mesangial and tubular epithelial cells which induces cytokines, IL-6 and TNF-α production in glomerular mesangial and tubular epithelial cells in diabetic kidney. Antioxidants inhibit high glucose induced transforming growth factors and extra cellular matrix expression in glomerular mesangial and tubular epithelial cells, which ameliorate features of diabetic nephropathy, suggesting that oxidative stress plays an important role in diabetic renal injury causing diabetic nephropathy. Journal of Chitwan Medical College 2013; 3(1): 1-4 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8456